Development of immediate feedback software for optimising glide performance and time of initiating post-glide actions - Naemi, R.; Aritan, S.; Goodwill, S.; Haake, S.; Sanders, R. (The Engineering of sport 7, Volume 1, 2008)
Performance in Starts and turns is a major contributor to success in swimming and is influenced greatly by the glide efficiency and the timing of commencing the post-glide action (including kick in all strokes and the underwater pull in breaststroke Starts and turns). The main aim of this research is to develop and test 'user friendly' Software for providing immediate feedback to swimmers and coaches to optimise glide performance and time of initiating post-glide actions in Starts, turns, and the glide phase of the breaststroke. The developed Software reads the video file of a glide followed by the post-glide action (PGA) gathered from a single underwater camera positioned perpendicular to the swimmer's trajectory path. A set of body markers are digitised to provide the records of the displacement data. The mathematical model based on the 'hydro-kinematic method' (Naemi, 2007) is coded in MATLAB to calculate the glide efficiency parameters, reconstructed instantaneous velocity, and the actual and optimal times and distances of commencing post-glide action using the raw displacement. A Graphic User Interface with user friendly icon based System enables the results to appear in an aesthetic and effective screen display, which includes a video replay, displacement and velocity graphs, and tabulated results. Early tests revealed that the effectiveness of the 'Hydro-kinematic' method in 'fine-tuning' performance can potentially be improved by the developed Software that enables rapid turnaround of results. The accompanying video replay enables qualitative assessrnent of postures and orientations enabling refinement in subsequent trials. The information from the Software is also particularly important in predicting the exact timing for initiating the post glide action for a particular swimmer with a distinct glide efficiency and post-glide performance.